IDNStudy.com, ang iyong destinasyon para sa mga maaasahang sagot. Makakuha ng impormasyon mula sa aming mga eksperto, na nagbibigay ng detalyadong sagot sa lahat ng iyong mga tanong.
Answer:
To find the factor of the expression \(11r + 15 = -2r\), we'll first solve the equation for \(r\).
1. **Combine like terms**:
Move the \(2r\) to the left side of the equation by adding \(2r\) to both sides.
\[11r + 15 + 2r = 0\]
\[13r + 15 = 0\]
2. **Isolate \(r\)**:
Subtract 15 from both sides.
\[13r = -15\]
3. **Solve for \(r\)**:
Divide both sides by 13.
\[r = -\frac{15}{13}\]
So, the solution is \(r = -\frac{15}{13}\).
In terms of factors, if you are looking for the factors of the left-hand expression \(11r + 15 + 2r\), it can be factored as:
\[13r + 15 = 13(r + \frac{15}{13})\]
This means that \(13(r + \frac{15}{13})\) is a factorized form, with \(13\) and \(r + \frac{15}{13}\) being factors.